Rapunzel syndrome, endoscopy solves the enigma: a case report - Ahmed Ramadan; Nancy A. Ahmed; Mohammed. N. Abdelaziz; El-Sayed Abou El-Magd (The Egyptian Journal of Internal Medicine)
Abstract Trichobezoars retain undigested material in the stomach, usually hair or hair-like fibers. Trichobezoars can cause gastrointestinal obstruction and Rapunzel syndrome, a perforation linked to pressure necrosis when they spread into the small intestine. This case study features a 16-year-old female patient complaining of epigastric pain. Computed tomography and abdominal ultrasonography yielded inconclusive results. A sizable clump of hair that stretched from the gastric body to the duodenum was seen on the upper endoscopy. The patient was first referred to a surgeon to have the hair removed, and then to the psychiatry department.